EKSISTENSI WARALABA (FRANCHISE) MENURUT PERATURAN PEMERINTAH NO. 42 TAHUN 2007 SEBAGAI PERJANJIAN INNOMINAAT - Asuan, Asuan (Faculty of Law, University of Palembang, 2017)
This research with normative juridical method. The juridical approach is the approach to the problem by looking in terms of the prevailing laws and regulations regarding the law of the treaty, the existence of Franchise (franchise) according to Government Regulation no. 42 of 2007 as an Innominaat Agreement